Association between periodontitis and cardiovascular disease - Duniya Khan, Syed Khawaja Muhammad, Mehreen Khaliq, Rana Modassir Shamsher Khan, Shamima Abdullah, Sadaf Raffi (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Association between clinical periodontitis and incident cardiovascular events was prospectivelyevaluated in a cohort of 250 middle-aged adults free of known cardiovascular disease at baseline.Periodontal status, including clinical attachment loss (CAL), probing depth, bleeding on probing(BOP), and serum inflammatory markers